Pengaruh Website Aesthetics, Perceived Benefit, dan E-Satisfaction terhadap E-Trust pada Pengguna Blibli di Kota Semarang - Lailatul Qodria Ramadina; I Made Sukresna (Diponegoro Journal of Management, 2026)
This study aims to analyze and examine the effects of website aesthetics and perceived benefit on e-satisfaction and e-trust of Blibli users in Semarang City. Along with the rapid growth of the e-commerce industry, understanding the factors that influence customer satisfaction and trust has become increasingly important for companies to maintain competitiveness. Website aesthetics and perceived benefit are considered key factors in shaping user experience, which may subsequently influence users’ satisfaction and trust. This research employs a quantitative approach using a survey method. The sample consists of 240 Blibli users in Semarang City selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS version 24 to examine the relationships among the variables in the research model. The results indicate that website aesthetics has a positive and significant effect on both esatisfaction and e-trust. Perceived benefit is found to have a positive and significant effect on e-satisfaction but does not significantly affect e-trust. Furthermore, e-satisfaction has a positive and significant effect on e-trust. These findings suggest that user satisfaction plays a crucial role in building trust in e-commerce platforms and highlight the importance of website aesthetics and perceived benefits in enhancing user experience.